Comparative analysis of the franchise services marketing mix: a study on Agua Doce Express and Agua Doce Master - Mendes de Oliveira, Thamara Cristina [UNESP]; Pigatto, Gessuir [UNESP]; Camargo Ferraz Machado, Joao Guilherme de [UNESP] (Univ Federal Campina Grande, Centro Ciencias Juridicas & Sociais, 2020)
Choosing the path to be used to deliver products and services to the intended audience is one of the key decisions for organizations or all efforts employed to produce the goods and services will be in vain. However, different distribution channels require different strategies that need to be well aligned to deliver value to the customer. This article aims to analyze the marketing strategies involved in the development of a new marketing channel for the Agua Doce Sabores do Brasil Group. Specifically, we sought to analyze the marketing compound of the Water Sweet Express and Sweet Water Master franchise models. It was noted that the business focus of this study differ in the initial investment, target audience, format of products offered, price, franchisee profile, physical structure and process. Thus, as they reach different consumer profiles, there is less likelihood of conflicts between the two distribution formats. The introduction of the new franchise format will enable the company to expand its market, reaching a new customer profile. However, the creation of the new business model will require the franchisor to better strategic planning and management of the franchisees in order to be successful.
Keywords: Distribution Channels; Marketing mix; Franchising